1997
DOI: 10.1046/j.1471-4159.1997.69041499.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Mesencephalic Dopamine Neurons by Anticancer Drug Cytosine Arabinoside

Abstract: Nanomolar concentrations of cytosine arabinoside (ara-C), a structural analogue of 2 '-deoxycytidine (2'dC) used in the chemotherapy of cancer, proved to be highly effective in preventing the death of postmitotic dopaminergic neurons that occurs spontaneously by apoptosis in mesencephalic cultures. The rescued cells were totally functional and highly differentiated. The trophic/neuroprotective effects of ara-C were (1) specific for dopaminergic neurons; (2) long-lived, remaining detectable several days after w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…1C) that occurs spontaneously and progressively in this culture model (Michel and Agid, 1996;Michel et al, 1997~).…”
Section: Adenosine Exerts Trophic Effects On Dopaminergic Neuronsmentioning
confidence: 78%
See 1 more Smart Citation
“…1C) that occurs spontaneously and progressively in this culture model (Michel and Agid, 1996;Michel et al, 1997~).…”
Section: Adenosine Exerts Trophic Effects On Dopaminergic Neuronsmentioning
confidence: 78%
“…86/609 and with the local ethical committee guidelines for animal research. Cultures of postmitotic dopaminergic neurons were prepared from the ventral mesencephalon of embryonic day 15.5 Wistar rat embryos (Michel and Agid, 1996;Michel et al, 1997~). After dissection, mesencephalic tissue was mechanically dissociated and plated in polyethylenimine (1 mg/ml; Sigma)-precoated culture plates (24 wells) or Labtek glass chamber slides .…”
Section: Mesencephalic Culturesmentioning
confidence: 99%
“…The cultures were then treated with the dopaminergic neurotoxins 6-OHDA (6-hydroxydopamine) or MPP + (1-methyl-4-phenylpyridinium), or 6-OHDA or MPP + and 5-HD (5-hydroxydecanoic acid, see below). This method can enrich neurons to >85% purity (Michel et al 1997;Gao et al 2003).…”
Section: Primary Mesencephalic Culturesmentioning
confidence: 99%
“…Hence, the aplogical activity. Based on this notion, it is suggested that the usage of cultures with a significantly smaller extent reported to contribute to the loss of embryonic dopaminergic nigral cells in culture (21,62). Programmed cell of cell-cell contact than the organotypic FFRT approach might result in a more pronounced effect of creatine death occurring as a natural phenomenon in a biphasic pattern with a first peak of apoptotic dopaminergic neutreatment on dopaminergic neurons survival.…”
mentioning
confidence: 99%